Perspectives on the Reception of Immigrants in the Catalan Cross-Border Area (Franco-Spanish Border) - Carbonell, Eliseu; Casademont, Xavier; Palaudàrias, Josep-Miquel; Sabrià, Gautier (Anthropologica, 2020)
This article is based on ethnographic research in a cross-border region of Mediterranean Europe distributed between the French and Spanish states. Specifically, these are two neighbouring regions, with a shared historical past, where the presence of migrants crossing the border from south to north or arriving from other points of origin has initiated deployment of welcoming actions by humanitarian organisations and local administrations. However, these actions are in stark contrast to the very restrictive migration policies of the two states. The article explores the perspective of the agents who work in these organisations and how their work relates to the increasingly hostile climate, which is a result of the migration policies currently implemented by European states.